2012
DOI: 10.1002/mc.21980
|View full text |Cite
|
Sign up to set email alerts
|

Association of VEGF and KDR single nucleotide polymorphisms with colorectal cancer susceptibility in Koreans

Abstract: Vascular endothelial growth factor (VEGF) and its receptor kinase insert domain-containing receptor (KDR) play crucial roles in angiogenesis, which contributes to the development and progression of solid tumors. The aim of this study was to investigate the associations of VEGF (-2578C > A, -1154G > A, -634G > C, and 936C > T) and KDR (-604T > C and 1192G > A) polymorphisms with the development of colorectal cancer (CRC). A total of 882 participants (390 CRC patients and 492 controls) were enrolled in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…However, the + 936T allele increases the risk for CRC in Korean and Chinese populations (Bae et al, 2008;Wu et al, 2009). Similarly, Jang et al (2013aJang et al ( , 2013b found that VEGF GENE POLYMORPHISMS AND COLORECTAL CANCER the + 936T allele was associated with an increased susceptibility to CRC. In gastric cancer, Tzanakis et al (2006) found a strong association between the -2578AA, + 936CT, and + 936TT genotypes and a larger tumor size, and the -2578AA genotype was strongly correlated to poor differentiation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the + 936T allele increases the risk for CRC in Korean and Chinese populations (Bae et al, 2008;Wu et al, 2009). Similarly, Jang et al (2013aJang et al ( , 2013b found that VEGF GENE POLYMORPHISMS AND COLORECTAL CANCER the + 936T allele was associated with an increased susceptibility to CRC. In gastric cancer, Tzanakis et al (2006) found a strong association between the -2578AA, + 936CT, and + 936TT genotypes and a larger tumor size, and the -2578AA genotype was strongly correlated to poor differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…Although it has been indicated that VEGF could be a good marker for determining the risk of developing CRC and could be used as a therapeutic target for new molecular anticancer drugs (Hanrahan et al, 2003;Fernando and Hurwitz, 2004;Dassoulas et al, 2009;Vidaurreta et al, 2010), the data remain conflicting if VEGF gene polymorphisms are associated with the prognosis of CRC (Yamamori et al, 2004;Park et al, 2007;Bae et al, 2008;Maltese et al, 2009;Wu et al, 2009;Hansen et al, 2010b;Antonacopoulou et al, 2012;Jang et al, 2013b). Therefore, to test this hypothesis, we investigated possible associations between genetic variations at the -2578A > C, + 936C > T, and -460C > T polymorphic site in the VEGF gene, in patients who have had CRC compared to healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, KDR polymorphisms were widely studied in recent years. For example, Jang et al found KDR SNPs (1192G>A) could reduce the risk of colorectal cancer in Koreans [33]. KDR variation (rs2305945, G/T) can lead to ovarian hyperstimulation syndrome in Travis's research [34].…”
Section: Introductionmentioning
confidence: 99%
“…The VEGF 1612A allele was associated with increased gastric cancer risk [ 23 ]. The 936C > T polymorphism and its link to CRC susceptibility have been published by our laboratory and others [ 6 , 24 ]. The other three single nucleotide polymorphisms (SNPs) in the VEGF 3′-UTR, 1451C > T, 1612G > A, and 1725G > A, are poorly understood in the context of their genetic contributions to CRC susceptibility.…”
Section: Introductionmentioning
confidence: 99%